-3(3x-4)-(2-2x)=10

Simple and best practice solution for -3(3x-4)-(2-2x)=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(3x-4)-(2-2x)=10 equation:



-3(3x-4)-(2-2x)=10
We move all terms to the left:
-3(3x-4)-(2-2x)-(10)=0
We add all the numbers together, and all the variables
-3(3x-4)-(-2x+2)-10=0
We multiply parentheses
-9x-(-2x+2)+12-10=0
We get rid of parentheses
-9x+2x-2+12-10=0
We add all the numbers together, and all the variables
-7x=0
x=0/-7
x=0

See similar equations:

| 9(2x+1)–4(x–6)=6(2x+1)+5(x–6) | | 4(2x—3)-(7x+4)=2 | | 7y-10=2y-6 | | -7y^2-45y+28=0 | | 5n-(2n+5)=0 | | 2x+7+3x-11=x+40 | | -5(6-3x)-7(3+7x)=-51 | | 1/4x−5=9 | | 2(8y+7/3)-5y=8 | | 7r^2+5r=0 | | x+15+10x+7=88 | | 0.05x=−0.25 | | 0.05x=−0.25. | | -5x+24=-(2x-3) | | n32n+6n23n=O(n32n) | | -5x-5(7x+8)=-320 | | 2x+3x-5+7=10x+-6x-4 | | -6-3x=3x-4(-5-5x) | | 3+2x-(×+1)=3×-6 | | -6(5x+2)=228 | | 10x+8x+6x=96 | | 6x-9=8x-31 | | 2(2x-3)=4x-78 | | 6(6x=6)-5=1+6x | | 1/2(x+2)=1/3(x+3) | | 11/4x+12=155 | | 6x=4x+1.2 | | (4y-7)+3y+26=180 | | .3=-4x+5/5x-4 | | 4(1+4x=-19-7x) | | 4(1+4x=-19-7x | | 5(x+2)=8(2x+1)+2 |

Equations solver categories